(untitled) (Third Sector Social Economic Review, 2017)
The use of cooperatives as a powerful instrument in setting the people who are in majority but economically weak in motion and enabling them to contribute to development becomes more important and is included in development plans. 82.5% of agricultural cooperatives in Turkey are agricultural development cooperatives and irrigation cooperatives. It is possible for family-owned enterprises to procure agricultural input, sell their products at reasonable prices, fulfill their expectations and be sustainable only by means of gathering under the umbrella of agricultural cooperatives. Kocaeli, which is a province with the highest national income in Turkey, has a significant place in national economy in terms of contribution to industry and service sectors. Industry and service sectors predominate the economy of Kocaeli. However, the province has an ecosystem suitable for agricultural production, the basic needs of her rapidly increasing urban population have to be met, and the majority of her sub-districts and villages - comprising 6.35% of the population – make a living from agriculture and stockbreeding. In addition to these, putting forth the situation of agricultural cooperatives, which play an essential role in agricultural development, for consideration makes the subject important. The Agricultural Development Cooperative of Çavuşlu village located in Derince district of Kocaeli province serves as a model in demonstrating the contributions of cooperatives in rural areas. Çavuşlu Agricultural Development Cooperative operates in the fields of raw milk and cattle feed. The purpose of this study is to identify the operational and organizational problems encountered by development cooperatives in rural areas, analyze the structure of cooperation in detail and propose solutions.